Prevalence of Tobacco Consumption in a Rural Community of Bangladesh - Ahmed, Shaila; Akter, Masuma; Mahzabeen, Rishad; Sayeed, Samia; Momtaz, Hasina; Sayeed, MA (Ibrahim Medical College Journal, 2009)
This cross sectional study was conducted in a rural community of Sreepur Thana during the month of November 2007. The objective of this study was to estimate the prevalence of tobacco consumption in the study area and observe some other associated variables. Respondents of both sexes aged 15 years and above were considered. The estimated sample size was 550 out of which 426 were found to be consumers of tobacco. Majority of the study population were males (68.4%). Illiteracy was found in 34.7% of the respondents. Most of them had some type of small business (38.2%) and a monthly expenditure between Tk.3001-6000 in 44% of the households. Prevalence of tobacco usuer was estimated to be 77.5%. Of them, 59% were smokers and 41% chewers. The most common form of smoking and chewing was found to be cigarette (69%) and jarda (94.6%) respectively. A large percentage of the respondents (94%) knew about the adverse health effects caused by consumption of tobacco. Ibrahim Med. Coll. J. 2008; 2(2): 58-60 Key Words: Tobacco consumption, smoking, rural community. doi: 10.3329/imcj.v2i2.2939